New sparse array for non‐circular sources with increased degrees of freedom. Issue 8 (20th January 2021) - Shaikh, Abdul Hayee; Dang, Xiaoyu; Khoso, Imran. A.; Huang, Daqing
Abstract: Recently, sparse arrays have received considerable attention as they provide larger array aperture and increased degrees‐of‐freedom (DOFs) compared to uniform linear arrays. These features are essential to enhance the direction‐of‐arrival estimation performance. However, most of the existing sparse arrays are mainly designed for circular sources and realize limited increment in DOFs for non‐circular sources. In this letter, a new sparse array configuration for non‐circular sources is presented, which significantly increases the achievable DOFs and improves the direction‐of‐arrival estimation performance. The proposed geometry comprises two effectively configured uniform linear arrays that exploit the characteristics of non‐circular sources and extend the array aperture. For a given number of sensors, its virtual array is advantageously a hole‐free uniform linear array. Moreover, the precise sensor locations, achievable DOFs, and optimal distribution of physical sensors are determined analytically by closed‐form expressions. Owing to these benefits, the proposed array efficiently resolve multiple sources in under‐determined conditions and achieves better direction‐of‐arrival estimation performance than its counterpart structures. Simulation results validate the superiority of the proposed configuration.